The Use of Porter’s Corporate Social Responsibility Strategy for Hospital Sustainability - Avininda Dewi Nindiasari; Andini Larasati Widodo; Amara Mulia Lumaku (Jurusan Akuntansi Politeknik Negeri Malang, 2023)
The Use of Porter’s Corporate Social Responsibility Strategy for Hospital Sustainability Purpose: To describe the sustainability strategy at Sehat Medika Hospital Method: This is qualitative research using Porter's CSR strategy which was obtained through interviews, observation and document review using triangulation techniques. Results: The results show that Sehat Medika Hospital has implemented CSR activities. The strategy made also describes the sustainability of the Hospital Novelty: This paper is a pioneering initiative in looking at the extent to which public hospitals are carrying out economic, social, and environmental activities in a sustainable manner through Porter's CSR strategy. Contribution: Through the preparation of a sustainability strategy, it is expected to be able to provide better accountability for the sustainability of the Sehat Medika Hospital. Penggunaan Strategi Corporate Social Responsibility Porter untuk Keberlangsungan Rumah Sakit Tujuan: Mendeskripsikan strategi keberlanjutan di Rumah Sakit Sehat Medika Metode: Penelitian kualitatif ini menggunakan strategi CSR Porter yang diperoleh melalui wawancara, observasi dan telaah dokumen dengan menggunakan teknik triangulasi. Hasil: Hasil penelitian menunjukkan bahwa RS Sehat Medika telah melaksanakan kegiatan CSR. Strategi yang dibuat juga menggambarkan keberlanjutan Rumah Sakit Kebaruan: Makalah ini merupakan inisiatif perintis dalam melihat sejauh mana rumah sakit umum melakukan kegiatan ekonomi, sosial, dan lingkungan secara berkelanjutan melalui strategi CSR Porter. Kontribusi: Melalui penyusunan strategi keberlanjutan diharapkan mampu memberikan akuntabilitas yang lebih baik untuk keberlanjutan Rumah Sakit Sehat Medika.